Toward Migration Transition in Romania - Cristian Incaltarau (CES Working Papers, 2012)
Most studies regarding the contribution of migration to development are limited to an isolated analysis of the economic effects of migration. But the migration process is in turn influenced by other processes. So a wider framework including migration and other processes of development would be more appropriate. The experience of South European and East Asian countries have shown us that, during development, countries can change their migration profile from emigration to immigration. The present paper shows the stages of the migration transition experienced by these countries trying to match them with Romania's experience. So, focusing on the case of Romania, this paper examines the evolution of international migration starting with 1990, in the context of the broader transition process, offering prospects regarding a possible migration transition in this case as well.
Keywords: F22; O15; 330; international migration; development; migration transition; Romania Romania